Immunogenicity of chitosan coupled heat killed and fusion protein vaccine of Mycobacterium avium subsp. paratuberculosis - VIJAYARANI, K; SUDHA, S; ABIRAMI, B; PRIYADHARSHINI, C V; KUMANAN, K (The Indian Journal of Animal Sciences, 2021)
In search for better vaccine candidates for Johne’s disease, chitosan nanoparticle coupled heat killed whole cell and fusion protein (Antigen 85A+85B) vaccines were developed using a local isolate of Mycobacterium avium subsp. paratuberculosis. Immunization studies in goats indicated that the heat killed whole cell vaccine and the fusion protein vaccine were found to be safe and resulted in Th1 and Th2 responses. Antibody response was significantly higher in the heat killed whole cell immunized animals than those received the fusion protein. Significant increase in heat killed whole cell MAP and fusion protein specific IFN-Î³ gene expression was detected in the immunized animals in contrast to the controls. The response was significantly higher with the heat killed whole cell MAP than the fusion protein. The adjuvant effect of chitosan nanoparticles was clearly evident in the second trial wherein the animals were observed for a longer period of 24 weeks. With increased IFN-Î³ and antibody levels, vaccinated animals responded well as compared to the control ones and the response was better in heat killed whole cell vaccine.